Gender-based equality in sport and women's presence in sport and sports leadership structures matrix 1.0 nation reports: a protocol for national and global annual report - Kascelan, B.; Katanic, B.; Govindasamy, K.; Geanta, V. A.; Baltean, A. I.; Mitrovic, M.; Masanovic, B. (Frontiers in Sports and Active Living, 2025)
This protocol was developed to facilitate the collection of up-to-date data and produce a comprehensive annual assessment of gender-based equality in sport and the representation of women in sports and leadership roles. Its goal is to provide evaluators with a standardized methodology for identifying and assessing key indicators related to gender equality and women's participation in sport at national, regional, and global levels. By focusing on a range of indicators, this protocol aims to highlight the current state of gender representation in sport and identify specific barriers to achieving equality. The protocol includes 19 sociodemographic indicators, accessible online, to characterize the demographic profile of participating countries. Additionally, it proposes 20 content indicators specifically focused on assessing women's presence in sport and leadership roles, as well as policies promoting gender equality. Each content indicator will be evaluated through separate analyses using a ten-point grading scale, allowing for a nuanced understanding of challenges and progress in this area. To ensure a dynamic connection between research and practice, the protocol encourages national evaluators to meet annually, producing national reports known as National Reports. These reports will offer detailed and ongoing assessments of gender equality in sport, with outcomes designed to inform policy development and advance gender equity in sports and leadership structures.